Particle fluxes in the Kara Sea and Ob and Yenisey estuaries. - Lisitzin, Alexander P; Shevchenko, Vladimir P; Vinogradov, Mikhail E; Severina, Olga V; Vavilova, Valentina V; Mitskevich, Irina N (PANGAEA, 1995)
Sedimentary particle fluxes in the Kara Sea and in the Ob and Yenisey estuaries were first estimated and particulate matter composition was studied in September 1993 during Cruise 49 of R/V Dmitry Mendeleev. Twenty three bottom stations with sediment traps were deployed, and samples were collected from 13 stations. Particle fluxes ranged from 9.0 to 62.6 mg/m**2/day to the north of the Ob and Yenisey estuaries and were 18.7 to 62.0 mg/m**2/day in the southwestern part of the Kara Sea. Fluxes were up to 1321 mg/m**2/day in the Ob estuary and up to 22156 mg/m**2/day in the Yenisey estuary. Organic matter fluxes were estimated as 0.71-3.29, 4.28-9.04, 26.7, and 368 mg/m**2/day, respectively. Particulate matter is largely represented by pellets of planktic Crustacea and by "sea snow" flakes mainly composed of diatoms. Rapidly settling particles are extensively inhabited by bacterial flora.
(Table 1) Vertical fluxes of sediment matter and organic carbon in the Kara Sea and in the Yenisey and Ob estuaries
Keywords: Archive of Ocean Data; ARCOD; Carbon, organic, particulate flux per day; Carbon, organic, total; Date/Time of event; Date/Time of event 2; DEPTH, water; DM49; DM49-4382ST; DM49-4386ST; DM49-4389ST; DM49-4394ST; DM49-4395ST; DM49-4396ST; DM49-4400ST; DM49-4401ST; DM49-4402ST; DM49-4403ST; DM49-4404ST; DM49-4405ST; DM49-4415ST; Dmitry Mendeleev; Duration, number of days; Gulf of Yenisey; Kara Sea; Obskaya Guba; Primary production of carbon per area, daily; Sample mass; SPASIBAIII; Total mass flux per day; Trap, sediment; TRAPS; trap sample; Weighing dry trap material; Wet chemistry; Yenisey River